Mitochondrial replacement therapy - a new remedy for defects in reproduction - PAL, ARUNA; BANERJEE, SAMIDDHA (The Indian Journal of Animal Sciences, 2018)
Mitochondria is an important subcellular organelle with the prime function being energy metabolism and supply of energy to the body cells for carrying out the vital functions. Energy is the primary requisite for the reproductive organs of both male and female for carrying out the normal functions. In the present article, we have described how mutation in mitochondrial DNA lead to defects in male and female reproduction. Mitochondria is an integral part of the mid-piece of sperm and also has role in other parts of male reproductive system. Similarly, mitochondrial DNA has role in female reproductive system including ovulation, zygote activation, fertilization, oocyte maturation and embryo development. Mitochondrial defect are collectively named as "mystondria" (mysterious diseases of mitochondria) and may be corrected through mitochondrial replacement therapy, popularly known as three parent baby concept, since there are no other scope for cure or treatment. Two approaches for mitochondrial replacement therapy are pronuclear transfer and spindle transfer. The first three parent baby was developed in April 2016 through mitochondrial replacement therapy. The present review is aimed at functional relevance of three-parent baby concept in animal reproduction.